How partisan is the press? Multiple measures of media slant - Joshua S. Gans; Andrew Leigh (Institute for the Study of Labor (IZA), 2011)
We employ several different approaches to estimate the political position of Australian media outlets, relative to federal parliamentarians. First, we use parliamentary mentions to code over 100 public intellectuals on a left-right scale. We then estimate slant by using the number of mentions that each public intellectual receives in each media outlet. Second, we have independent raters separately code front-page election stories and headlines. Third, we tabulate the number of electoral endorsements that newspapers give to each side of politics in federal elections. Overall, we find that the Australian media are quite centrist, with very few outlets being statistically distinguishable from the middle of Australian politics. It is possible that this is due to the lack of competition in the Australian media market. To the extent that we can separate content slant from editorial slant, we find some evidence that editors are more partisan than journalists.
urn:nbn:de:101:1-2012010913766
Keywords: D72; L82; 330; media slant; media bias; competition; economics of elections; Kommunikationsmedien; Öffentliche Meinung; Parteipolitik; Wahlkampf; Wettbewerb; Australien